2013
DOI: 10.1111/ppa.12136
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a new introduction of the pitch canker fungus Fusarium circinatum in South Africa

Abstract: AfricaFusarium circinatum causes pitch canker of Pinus species in many parts of the world. The fungus was first recorded in South Africa in 1990 as a pathogen of P. patula seedlings and emerged later as a pathogen of established plantation trees, especially P. radiata in the Western Cape Province (WCP). In this study the population biology of F. circinatum in the WCP was explored. The aim was to determine the possible origin and reproductive mode of the pathogen, with the ultimate intention of informing diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 41 publications
2
57
0
Order By: Relevance
“…The first record of the pathogen affecting established plantation trees was in 2005, when the typical pitch canker symptoms were observed on 5‐ to 9‐year‐old Pinus radiata trees in a plantation in the Western Cape Province (WCP; Coutinho et al ., ). Pitch canker has subsequently also been reported from 12‐ to 15‐year‐old P. radiata trees in other plantations in the Province, as well as on Pinus greggii trees in the Eastern Cape Province (ECP) and the KwaZulu‐Natal Province of South Africa (Steenkamp et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…The first record of the pathogen affecting established plantation trees was in 2005, when the typical pitch canker symptoms were observed on 5‐ to 9‐year‐old Pinus radiata trees in a plantation in the Western Cape Province (WCP; Coutinho et al ., ). Pitch canker has subsequently also been reported from 12‐ to 15‐year‐old P. radiata trees in other plantations in the Province, as well as on Pinus greggii trees in the Eastern Cape Province (ECP) and the KwaZulu‐Natal Province of South Africa (Steenkamp et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Little is known regarding the population biology of F. circinatum responsible for the pitch canker outbreaks in South African Pinus plantations. The results of a single previous study revealed significant diversity among isolates originating from diseased P. radiata trees in WCP plantations, but unlike the situation in Pinus nurseries, these populations appeared to be more structured and to reproduce clonally (Steenkamp et al ., ). This previous study also suggested that the WCP plantations originated from distinct introductions of the pathogen into the region (Steenkamp et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations